Peran Celebrity Endorser Sebagai Strategi Pemasaran Guna Meningkatkan Daya Saing UMKM Di Era Digital - Risa Yanuar Erika Putri; Dila Fitriana Paramita; Dwi Astuti (CV. ITTC INDONESIA, 2025)
This study aims to analyze the role of celebrity endorsement as a marketing strategy in improving the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the digital era. In the context of an economy that is increasingly affected by the development of information and communication technology, MSMEs face the challenge of adapting to effective ways of marketing. Celebrity endorsement has become one of the popular promotional methods, especially on social media, as it can increase consumer trust and attract the attention of the target market. The research method used is descriptive qualitative with secondary data. The results showed that the use of celebrities in promotions not only increased brand awareness, but also contributed to an increase in consumer buying interest. Celebrities who have high credibility and strong appeal can influence purchasing decisions, so MSMEs are advised to choose endorsers that match the characteristics of their products and audiences. In addition, direct interaction between celebrities and consumers through social media also contributes to increased customer engagement and loyalty. This research confirms that celebrity endorsement strategies can be an effective tool for MSMEs to compete in the digital market. The impact of celebrity endorsers on consumer behavior is able to increase product sales because fans of these celebrity endorsers have high loyalty to id.